2007
DOI: 10.1159/000108121
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Adhesion Characteristics of Acrylic Intraocular Lens Materials and Posterior Capsule Opacification

Abstract: Purpose: To investigate the relationship between the adhesion characteristics of similarly designed hydrophobic acrylic intraocular lenses (IOLs) and posterior capsule opacification (PCO). Methods: Three similarly shaped hydrophobic acrylic IOLs with a sharp-edged optic were used. Adhesive force of IOLs was measured with a tackiness tester. Human lens epithelial cells (LECs) were grown on each IOL for 48 h. LECs were then stained with crystal violet, which served as an index of the amount of cells attached to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…The hydrophobic acrylate surface has bioadhesive characteristics that improve adhesion of the IOL to the capsular bag and thus result in less PCO. 33,34 The biofilm formation on the Meridian HP60M hydrophilic IOL was less than that reported for PMMA IOLs and hydrophobic IOLs. 10 The reason may be the formation of a monolayer of LECs, which bonds the bioactive hydrophobic acrylic IOL to the posterior lens capsule.…”
Section: Discussionmentioning
confidence: 79%
“…The hydrophobic acrylate surface has bioadhesive characteristics that improve adhesion of the IOL to the capsular bag and thus result in less PCO. 33,34 The biofilm formation on the Meridian HP60M hydrophilic IOL was less than that reported for PMMA IOLs and hydrophobic IOLs. 10 The reason may be the formation of a monolayer of LECs, which bonds the bioactive hydrophobic acrylic IOL to the posterior lens capsule.…”
Section: Discussionmentioning
confidence: 79%
“…Fibronectin was also found to adhere more to hydrophobic acrylic IOLs than to PMMA, silicone, or hydrophilic acrylic IOLs. 48,49 Another consideration is that IOLs of the same material from different manufacturers can have different surface properties. Using 3 hydrophobic acrylic IOLs, Katayama et al 49 showed how the adhesiveness of disk optics of the same material and design from a single manufacturer can change significantly because of differences in the surface energy caused by modification of the constituents of the copolymer.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that modifying the surface energy of the IOL optic can influence the adhesiveness of the material. 49,50,51 Further AFM studies that directly compare hydrophobic acrylic IOLs from different manufacturers are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…32 The adhesive force of lens material also influences PCO development-the more highly adhesive hydrophobic lens materials seem to inhibit lens epithelial cell migration. 33 Other important factors in limiting PCO formation include surgical technique, capsulorhexis overlap of the optic, and control of inflammation.…”
Section: ' Lens Biocompatibilitymentioning
confidence: 99%